Environmentally sustainable governance model to improve the ewaste management in Mexico City - Cano, Hugo Armando Fragoso (Open Science Journal, 2020)
In this age of technology, where the use of this is excessive and its exponential growth has given rise to a series of challenges and opportunities caused by the accumulation of waste electrical and electronic equipment in Mexico City. For its treatment, more practical approaches have been necessary, taking into account proper management and long-term well-being as a main element of sustainability. The objective of this work is to propose sustainable initiatives based on social, economic and environmental dimensions, based on the challenges faced by waste management of electrical and electronic equipment as one of the fields that contribute to the transition towards a sustainable society. Data from each dimension were analyzed to extract the most relevant challenges by reviewing the literature and identifying sources that relate them to the life cycle of electrical and electronic waste. As a result, a governance model for waste electronic and electronic devices was obtained to support environmental sustainability that identifies lines of action for the effective treatment of waste electrical and electronic equipment highlighting awareness, education, knowledge and regulations as well as processes environmental. From this it is concluded that the governance of waste electrical and electronic equipment is mandatory for the integration of economic, social and environmental factors to efficiently leverage efforts on environmental care.